Penyebaran Literatur KeIslaman di Pesantren: Kontestasi Ideologi dan Pasar di Jawa Timur - Mahzumi, Fikri; Kasno, Kasno; Kafabih, Abdullah; Cholily, Naufal (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2024)
This study aims to investigate the dissemination of Islamic literature in contemporary East Java, the efforts of Islamic literature publishers to transmit and embed their ideology, and the significance of this ideology in maintaining the profitability of the publishing industry. The research uses a descriptive qualitative approach, gathering primary data from publishing professionals and Islamic boarding schools in East Java. The phenomenological approach involves three stages of data reduction (phenomenological, eidetic, and transcendental). The findings reveal that ideology plays a crucial role in the success of the Islamic literature publishing business. Publishers employ strategic efforts and marketing techniques to identify and cater to market potential, including pre-press editing where content is selected based on the publisher's ideology. The demand for Islamic literature among consumers, particularly students in pesantren, is increasing, and publishers and distributors capitalize on this opportunity to maximize profits.